Implementación de un sistema web para gestión de biblioteca de la Unidad Educativa Guasaganda. - Portilla Peña, Karelis Isabela (2023)
The main objective of this project is to develop a library system for the Guasaganda Educational Unit, the purpose of this study is to implement the program in the library area based on the bibliographic material that is available; and because there are many books available to students. Therefore, there is a need to keep track of the information of the users who request books to broaden their reading and register authors, publishers, categories in the books and provide by returning these materials. In other words, the library area needed a system to manage, organize and facilitate the location of books when requested. Bidding methods such as interviews and surveys were used to collect data, analyze problems and obtain the system requirements that must be taken into account to correctly develop the system. By using tools such as the server-side programming language PHP and MySQL as the database administrator, we are able to execute and adhere to the plans developed through the Agile Scrum methodology. The system allows the automation of the book loan management process of the library of the Guasaganda Educational Units. Due to its ever-changing infrastructure, you can have a variety of books from different authors that students and teachers often request at the same time. KEY WORDS: Library, Web System, Book lending, Educational Unit, PHP, MySQL.